American fever : a novel - Aziz Amna, Dur E (New York : Arcade Publishing, 2022)
"For fans of Valeria Luiselli and Mohsin Hamid comes a fresh new perspective on coming-of-age as a Pakistani Muslim in rural America. "This is a fearless, exacting, essential work, and marks the debut of a thrilling new global voice."-Peter Ho Davies, author of The Welsh Girl. On a year-long exchange program in rural Oregon, sixteen-year-old Hira must swap Kashmiri chai for volleyball practice and understand why everyone around her seems to dislike Obama. A skeptically witty narrator, Hira finds herself stuck between worlds. The experience is memorable for reasons both good and bad; a first kiss, new friends, racism, Islamophobia, homesickness. Along the way Hira starts to feel increasingly unwell until she begins coughing up blood, and receives a diagnosis of tuberculosis, pushing her into quarantine and turning her newly established home away from home upside down. American Fever is a compelling and laugh-out-loud funny novel about adolescence, family, otherness, religion, the push-and-pull of home. It marks the entrance on the international literary scene of the brilliant fresh voice of Dur e Aziz Amna. "--
Keywords: FICTION / Coming of Age; FICTION / Muslim; Novels